2020
DOI: 10.3892/ijmm.2020.4620
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑16 inhibits endometrial stromal cell migration and invasion through suppression of the inhibitor of nuclear factor‑κB kinase subunit β/nuclear factor‑κB pathway

Abstract: Accumulating evidence has demonstrated that endometrial stromal cells (EScs) are responsible for the pathogenesis of endometriosis (Ems), which is characterized by the presence of functional endometrial-like tissues outside the uterine cavity. Abnormal expression of microRNAs (miRNAs) in EScs may be implicated in the etiology of Ems; however, the exact mechanisms have yet to be fully elucidated. The aim of the present study was to investigate the effects of miRNAs on EScs and the underlying mechanisms. Using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A molecular profiling study of CD44 and ALDH expressing endometrial tumor circulating cells found increased expression of NF-κB member RelA associated with tumor infiltration and EMT [ 58 ]. Consistently, miRNA-16-mediated suppression of RelA activation inhibited the invasion and migration of endometrial stromal cells often involved in endometrial pathogenesis [ 59 ]. Invasion and migration of endometrial cancer cells was also inhibited via IL-37b-mediated suppression of RelA, however it did not affect EMT [ 60 ].…”
Section: Targeting Signaling Pathways In Endometrial Cancer Stem Cellsmentioning
confidence: 90%
“…A molecular profiling study of CD44 and ALDH expressing endometrial tumor circulating cells found increased expression of NF-κB member RelA associated with tumor infiltration and EMT [ 58 ]. Consistently, miRNA-16-mediated suppression of RelA activation inhibited the invasion and migration of endometrial stromal cells often involved in endometrial pathogenesis [ 59 ]. Invasion and migration of endometrial cancer cells was also inhibited via IL-37b-mediated suppression of RelA, however it did not affect EMT [ 60 ].…”
Section: Targeting Signaling Pathways In Endometrial Cancer Stem Cellsmentioning
confidence: 90%
“…Interestingly, we found that a few of these miRNAs are commonly dysregulated in the gynecological diseases. For example, miR‐16 is abnormally expressed in EM and PCOS patients, and miR‐21 in ICP and PMOP patients (Fu et al, 2018; Jiang et al, 2019; Suarjana et al, 2019; Wang et al, 2020). Furthermore, miR‐146a‐5p was seen to be dysregulated in URSA, which is consistent with previous reports by Maccani et al (2010) (Zhao et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, Gu et al (2020) also showed 114 miRNAs to be differentially expressed in EM, among which 14 miRNAs were downregulated, which they proposed as potential biomarkers and therapeutic targets for the diagnosis and treatment of EM. miR-16, reported by Wang et al (2020), was seen to inhibit migration, adhesion, and invasion of primary endometrial stromal cells (ESCs) by suppressing the downstream gene IKKβ belonging to the IKKβ/NF-κB pathway. Other than miRNAs, lncRNAs are also found to be involved in EM such as CHL1-AS2 and LOC100505776 reported by Sun et al (2014).…”
Section: Ncrnas In Women's Healthmentioning
confidence: 99%
“…MiRNAs are ncRNAs that are 19-25 nucleotides in length and negatively regulate gene expression by binding to the 3′-untranslated regions of target mRNAs [59]. Four types of miRNAs, namely, miR-16, miR-138, miR-182, and miR-199a, directly target the key NF-κB signaling-related genes IKKβ (targeted by miR-138 and miR-182) and p65 (targeted by miR-16 and miR-199a) to inhibit NF-κB signaling, and their expression is downregulated in ectopic endometrium [60][61][62][63]. In contrast, two miRNAs, namely, miR-9 and miR-22, indirectly activate NF-κB signaling by repressing the expression of sirtuin 1 (SIRT1), an NAD (+)-dependent deacetylase, to reduce inflammatory responses in the ectopic endometrium [64,65].…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…In contrast, two miRNAs, namely, miR-9 and miR-22, indirectly activate NF-κB signaling by repressing the expression of sirtuin 1 (SIRT1), an NAD (+)-dependent deacetylase, to reduce inflammatory responses in the ectopic endometrium [64,65]. The overexpression of miR-16, miR-138, miR-182, and miR-199a or the inhibition of miR-9 and miR-22 can block NF-κB signaling and further repress inflammatory responses and the survival, migration, and invasion abilities of endometriotic cells [60][61][62][63][64][65].…”
Section: Noncoding Rnasmentioning
confidence: 99%